Peningkatan Kreativitas dan Kesadaran Lingkungan melalui Edukasi Pembuatan Ecoprint bagi Siswa di Desa Sumber Agung, Kecamatan Way Sulan, Kabupaten Lampung Selatan - Muhassin, Moh; Sulistyawati, Ayu (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
Environmental education is crucial to be introduced at an early age to enhance students' awareness ofsustainability. One creative and eco-friendly method is ecoprint, a printing technique that uses naturalmaterials such as leaves and flowers. This study aims to enhance students' creativity and environmentalawareness through an ecoprint-making education program for elementary school students in DesaSumber Agung, Kecamatan Way Sulan, Kabupaten Lampung Selatan. The study employed a descriptivequalitative method with a participatory approach. A total of 18 elementary students participated in aseries of ecoprint training activities, ranging from material collection to hands-on practice. The ecoprintprocess utilized local natural resources to create environmentally friendly designs on fabric. The findingsrevealed that students not only developed creative artistic skills but also gained a deeper understandingof the importance of environmental preservation. Utilizing local natural resources encouraged studentsto appreciate their surroundings more and explore creative ways to make use of them sustainably.